Beban Ganda Buruh Tani Perempuan di Jorong Limpato Nagari Kajai Kecamatan Talamau Kabupaten Pasaman Barat - Riva Dila Yarsiah; Alia Azmi (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2020)
This study aims to describe the phenomenon of the double burden endured by female farm workers in Jorong Limpato Nagari Kajai and the impact of the double burden on family and social activities in the community and to identify the involvement of the female farmworker's husband in domestic work. This research is a qualitative research with descriptive method conducted in Jorong Limpato Nagari Kajai Talamau District, West Pasaman Regency. The informants in this study were determined using purposive sampling technique. The type of data in this study consisted of primary and secondary data obtained through observation, interviews, and documentation studies. The results of the study show the phenomenon of the double burden faced by women farm workers can be seen from their productive, reproductive, and social roles in society. The positive impact of a double burden on the family is to increase the husband's income in meeting family needs, while the negative impact is the time to gather with the family and educate and supervise children is limited and the difficulty in allocating time to carry out their role creates pressure for farm laborers. The positive impact of a double burden on social activities in the community is women active in social activities in the community that are informal as at weddings and deaths, while the negative impact is the lack of interaction between women farm workers and community members, in addition to social activities held during the day women farm workers are rarely attended because to attend they are forced to leave their jobs. The involvement of the female farm worker husband in domestic work is very low due to the construction of community thought in Jorong Limpato which results in gender injustice against the female farm worker. interviews, and documentation studies. The results of the study show the phenomenon of the double burden faced by women farm workers can be seen from their productive, reproductive, and social roles in society. The positive impact of a double burden on the family is to increase the husband's income in meeting family needs, while the negative impact is the time to gather with the family and educate and supervise children is limited and the difficulty in allocating time to carry out their role creates pressure for farm laborers. The positive impact of a double burden on social activities in the community is women active in social activities in the community that are informal as at weddings and deaths, while the negative impact is the lack of interaction between women farm workers and community members, in addition to social activities held during the day women farm workers are rarely attended because to attend they are forced to leave their jobs. The involvement of the female farm worker husband in domestic work is very low due to the construction of community thought in Jorong Limpato which results in gender injustice against the female farm worker.